Parque Ecológico Tierra del Sol Reserva de Fauna y Flora Bogotá - Engativá (2022)
The urban project Park Ecologic land of the Sun Reserve of Fauna and Flora is developed from an environmental investigation in the City of Bogotá, Engativá locality. This town has three environmental nodes such as: the Bogotá River, the Florida Park and the Jaboque Wetland, key points in the environmental development of the city, but with different problems, for this reason a mixed methodology was carried out that determines the physical characteristics and As a next step, the territorial conclusions were taken and fieldwork was carried out with the community, generating surveys and participatory designs to determine possible solutions to the problems of pollution, insecurity and lack of public awareness in the context of the main nodes.